Chronic voluntary wheel running facilitates corticosterone response habituation to repeated audiogenic stress exposure in male rats - SASSE, SARAH K. (2008)
Voluntary exercise is associated with the prevention and treatment of numerous physical and psychological illnesses, yet the mechanisms by which it confers this protection remain unclear. In contrast, stress, particularly under conditions of prolonged or repeated exposure when glucocorticoid levels are consistently elevated, can have a devastating impact on health. It has been suggested that the benefits of physical exercise may lie in an ability to reduce some of the more deleterious health effects of stress and stress hormones. The present series of experiments provides evidence that voluntary exercise facilitates habituation of corticosterone but not adrenocorticotropin hormone responses to repeated stress presentations. After 6 weeks of running wheel access or sedentary housing conditions, rats were exposed to 11 consecutive daily 30 min presentations of 98 dB noise stress. Similar corticosterone responses in exercised rats and sedentary controls were observed following the first, acute stress presentation. While both groups demonstrated habituation of corticosterone secretory responses with repeated noise stress exposures, the rate of habituation was significantly facilitated in exercised animals. These results suggest that voluntary exercise may reduce the negative impact of prolonged or repeated stress on health by enhancing habituation of hypothalamo-pituitary–adrenocortical axis responses at the level of the adrenal cortex, ultimately reducing the amount of glucocorticoids the body and brain are exposed to.